Immunogold FIB-SEM: combining volumetric ultrastructure visualization with 3D biomolecular analysis to dissect cell-environment interactions - Gopal,S; Chiappini,C; Armstrong,J; Chen,Q; Serio,A; Hsu,C; Meinert,C; Klein,TJ; Hutmacher,DW; Stevens,M (Advanced Materials, 2019)
Volumetric imaging techniques capable of correlating structural and functional information with nanoscale resolution are necessary to broaden the insight into cellular processes within complex biological systems. The recent emergence of focused ion beam scanning electron microscopy (FIBSEM) has provided unparalleled insight through the volumetric investigation of ultrastructure; however, it does not provide biomolecular information at equivalent resolution. Here, immunogold FIBSEM, which combines antigen labeling with in situ FIBSEM imaging, is developed in order to spatially map ultrastructural and biomolecular information simultaneously. This method is applied to investigate two different cell–material systems: the localization of histone epigenetic modifications in neural stem cells cultured on microstructured substrates and the distribution of nuclear pore complexes in myoblasts differentiated on a soft hydrogel surface. Immunogold FIBSEM offers the potential for broad applicability to correlate structure and function with nanoscale resolution when addressing questions across cell biology, biomaterials, and regenerative medicine.